New Dipyrroloquinones from a Plant-Derived Endophytic Fungus Talaromyces sp. - Dandan Zhang; Xiaoqing Wang; Bo Liu; Shuhui Li; Yanlei Wang; Tao Guo; Yi Sun (Molecules, 2023)
Two new dipyrroloquinones, namely talaroterreusinones A (1) and B (2), together with four known secondary metabolites, terreusinone A (3), penicillixanthone A (4), isorhodoptilometrin (5), and chrysomutanin (6), were isolated from the solid culture of the endophytic fungus Talaromyces sp. by integrating mass spectrometry-based metabolic profiling and a bioassay-guided method. Their planar structures and stereochemistry were elucidated by comprehensive spectroscopic analysis including NMR and MS. The absolute configuration at C-1″ of terreusinone A (1) was established by applying the modified Mosher’s method. Compounds 1–6 were evaluated for anti-inflammatory activity and cytotoxicity. As a result, 1–3 inhibited the LPS-stimulated NO production in macrophage RAW264.7 cells, with IC50 values of 20.3, 30.7, and 20.6 µM, respectively. Penicillixanthone A (4) exhibited potent cytotoxic activity against Hep G2 and A549 cell lines, with IC50 values of 117 nM and 212 nM, respectively, and displayed significant antitumour effects in A549 cells by inhibiting the PI3K-Akt-mTOR signalling pathway.